2006
DOI: 10.3349/ymj.2006.47.2.179
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Magnetic-Activated Cell Sorting, Cytotoxicity and Preplating for the Purification of Human Myoblasts

Abstract: Although cultured myoblast transplantation has been extensively studied as a gene complementation approach to muscular dystrophy treatment, clinical success has still been limited. The inability to adequately isolate and purify myoblasts presents a major limitation to the production of sufficient myoblasts for engrafting purposes. This study attempted to purify myoblasts from primary culture by magnetic-activated cell sorting (MACS), complement-mediated cytotoxicity, and a preplating technique. As a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…To date, a number of researchers have reported several myoblast purification procedures to obtain a homogeneous myogenic cell culture, including density centrifugation, selective adhesion and chemical use of fibroblast growth inhibitors (Kao and Prockop, 1977;Yablonka-Reuveni et al, 1987;Blanton et al, 1999). Immunomagnetic techniques have recently been reported (Lequerica et al, 1999;Sinanan et al, 2004;Park et al, 2006) to purify myogenic cells from primary cultures by magnetic activated cell sorting, with good yields. Lequerica et al (1999) reported an increase in the percentage of myoblasts in mixed culture from 8.4% to more than 90% using this technique.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of researchers have reported several myoblast purification procedures to obtain a homogeneous myogenic cell culture, including density centrifugation, selective adhesion and chemical use of fibroblast growth inhibitors (Kao and Prockop, 1977;Yablonka-Reuveni et al, 1987;Blanton et al, 1999). Immunomagnetic techniques have recently been reported (Lequerica et al, 1999;Sinanan et al, 2004;Park et al, 2006) to purify myogenic cells from primary cultures by magnetic activated cell sorting, with good yields. Lequerica et al (1999) reported an increase in the percentage of myoblasts in mixed culture from 8.4% to more than 90% using this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Primary skeletal muscle stem cells were isolated from a M. vastus lateralis muscle biopsy as described (Orth et al, 2003;Park et al, 2006) (Fig. 1c).…”
Section: Generation Of Myoblast From Human Muscle Biopsiesmentioning
confidence: 99%
“…Cells were split using TrypLE (Life technologies). To enrich myogenic cells the pre-plating method described by Park and collaborators (Park et al, 2006) with some modifications was used. Briefly, cells were detached and then pre-plated in a gelatincoated flask.…”
Section: Differentiation Of Hipsc Into Myoblasts or Motoneuronsmentioning
confidence: 99%
“…For tissue engineers, knowing that final purity is essential for consistent tissue fabrication. Fluorescence activated cell sorting (FACS) and magnetic activated cell sorting (MACS) have been used to evaluate the success of the pre-plating process, leading researchers to consider whether they can be used to skip pre-plating and immediately sort instead [51,52]. …”
Section: Purificationmentioning
confidence: 99%
“…Research by the Blau laboratory demonstrated that semi-pure mouse myoblast populations may be isolated using MACS technology to select for α7 Integrin + cells, with similar purification levels as found with FACS [52]. Although MACS has been used in some cases to purify CD56 positive satellite cells [62], direct comparison of pre-plating and MACS indicated much greater purification using the pre-plating technique [51]. From these studies, it is clear that multiple markers are likely needed isolate a highly pure population.…”
Section: Purificationmentioning
confidence: 99%